2018
DOI: 10.13005/bpj/1533
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Medical Imaging Modalities and Challenges For Diagnosing Breast Cancer

Abstract: Breast cancer is the leading deadly cancer and most commonly diagnosed in women. New technologies in supplement to existing imaging modalities improve breast cancer screening. This article contributes to identify the high potential device that suggested high accuracy and reliable tool for breast screening and also to examine new screening modalities. An improved imaging system which ensures early detection, non-invasive and radiation free is expected in diagnosis. Numerous imaging modalities like positron emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Each imaging modality presents unique advantages and challenges in clinical practice. X-rays are extensively utilized for their accessibility and capacity to detect conditions such as pneumonia by visualizing areas of heightened lung density caused by fluid or inflammation [ 29 ]. CT scans provide detailed images and are instrumental in diagnosing complex conditions.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Each imaging modality presents unique advantages and challenges in clinical practice. X-rays are extensively utilized for their accessibility and capacity to detect conditions such as pneumonia by visualizing areas of heightened lung density caused by fluid or inflammation [ 29 ]. CT scans provide detailed images and are instrumental in diagnosing complex conditions.…”
Section: Reviewmentioning
confidence: 99%
“…Challenges in medical imaging modalities encompass managing large-scale datasets efficiently, ensuring reliable data interrogation from multiple sources, and optimizing deep learning models for precise diagnoses across diverse populations [ 30 ]. Incorporating machine learning techniques such as convolutional neural networks (CNNs) has significantly enhanced the speed and accuracy of diagnoses by automatically classifying imaging data based on computed parameters [ 29 ]. Additionally, emerging technologies such as thermography and electrical impedance tomography (EIT) provide non-invasive and radiation-free alternatives for early detection and risk assessment in conditions such as breast cancer [ 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…Ultrasound technology, which has been advancing, includes various methods such as color Doppler, power Doppler, contrast-enhanced US, 3D ultrasound, automated breast ultrasound (ABUS), and elastography. These methods have been increasing the sensitivity and specificity of conventional US to a maximum level [ 20 , 21 ].…”
Section: Imaging Modalities Used In Breast Lesionsmentioning
confidence: 99%
“… Various imaging modalities used for breast mass management, with ultrasound showing the highest sensitivity [ 20 , 21 ]. …”
Section: Figurementioning
confidence: 99%
“…Comprehensive research concerning the medical imaging modalities for diagnosing breast cancer [46] suggests that thermography is a superior imaging modality for dense breast tissues and their early detection. This finding is supported by previous research [47] which indicated that thermography could be correct from 8-10 years before mammography can detect a mass.…”
Section: A Potential Of Breast Thermogram Modalitymentioning
confidence: 99%